Front Cover: Quantum Dot Molecule Devices with Optical Control of Charge Status and Electronic Control of Coupling (Adv. Quantum Technol. 10/2022). Issue 10 (11th October 2022) - Bopp, Frederik; Rojas, Jonathan; Revenga, Natalia; Riedl, Hubert; Sbresny, Friedrich; Boos, Katarina; Simmet, Tobias; Ahmadi, Arash; Gershoni, David; Kasprzak, Jacek; Ludwig, Arne; Reitzenstein, Stephan; et al.
Abstract : The cover image shows a quantum dot molecule (QDM), in which the tunnel coupling is electrically controlled. In article number 2200049, Frederik Bopp, Jonathan J. Finley, and co‐workers propose and demonstrate a measurement scheme allowing for a simultaneous optical charge state and electric coupling control of single QDMs. These results pave the way towards generating 2D photonic cluster states from solid‐state emitters. Cover image by Christoph Hohmann (MCQST).